Susceptibility of A. fumigatus‐specific T‐cell assays to pre‐analytic blood storage and PBMC cryopreservation greatly depends on readout platform and analytes. Issue 8 (11th June 2018) - Lauruschkat, Chris D.; Wurster, Sebastian; Page, Lukas; Lazariotou, Maria; Dragan, Mariola; Weis, Philipp; Ullmann, Andrew J.; Einsele, Hermann; Löffler, Jürgen
Summary: Mould‐specific T cells detectable by flow cytometry or ELISPOT were proposed as a novel biomarker in invasive aspergillosis. To define protocols facilitating sample shipment and longitudinal analysis, this study evaluated the susceptibility of different functional assays for A. fumigatus ‐specific T‐cell quantification and characterisation to pre‐analytic delays. PBMCs from 6 healthy donors were analysed after immediate isolation, after 6 hours whole blood storage or after cryopreservation using 3 different common media. Functional responses to A. fumigatus lysate stimulation were comparatively assessed by flow cytometry, ELISPOT and 14‐plex cytokine assay. After 6 hours pre‐analytic storage, all functional assays showed reduced detection rates, higher coefficients of variation (CV) and widely varying individual recovery indices of specific T‐cell response. While cryopreservation resulted in sufficient yields and largely unaltered cellular composition, outcomes of functional readouts significantly differed from freshly processed samples. For CD154‐based flow cytometry, only cryopreservation in RPMI supplemented with autologous serum resulted in satisfactory detection rates and CVs. For ELISPOT and cytokine secretion assays, none of the cryopreservation protocols provided sufficient concordance with immediately processed samples. Even using the same readout platform, individual analytes widely varied in their susceptibility to cryopreservation, highlighting that distinct optimisation is required depending on the downstream assay.